PENGARUH ATMOSPHERIC EXPERIENCES TERHADAP LOYALITAS PELANGGAN DI THE RESTAURANT PADMA HOTEL BANDUNG - Soniawati, Nita; Abdullah, Taufik (THE Journal : Tourism and Hospitality Essentials Journal, 2016)
The tourism and hospitality industry is growing rapidly. This notion has led to a tight competition among the industry. To survive the competition, many industries have tried hard to keep the customers' loyalty because acquiring the new customer is even harder than maintaining the loyal customers. Padma Hotel Bandung has operated a restaurant. However, the data showed that there was a 6.1% decrease on the number of tourist who dined in there. This study aims to examine the influence of atmospheric experiences of the customer loyalty. The sample size was 100 respondents who were the members of Padma Privilege Dining Club. The data were analyzed by multiple linear regression techniques. The independent variable of this research was the atmospheric experience of the restaurant that consisted of ambience, interaction, and design as the dimensions. Furthermore, the dependent variable of this research was the customer loyalty. The result showed that the interaction as the atmospheric experience variable got the highest rating score. However, the ambience dimension was at the lowest position. Finally, it was concluded that the atmospheric experience had a positive influence to the customer loyalty.